2011
DOI: 10.1111/j.1440-1681.2011.05556.x
|View full text |Cite
|
Sign up to set email alerts
|

N‐Methyl‐d‐aspartate receptor modulators block hyperalgesia induced by acute low‐dose morphine

Abstract: 1. Following opioid-induced antinociception in mice, hyperalgesic responses may be observed. The present study was designed to evaluate the effect of different N-methyl-d-aspartate (NMDA) receptor modulators (magnesium, dextromethorphan, d-serine) on the development of morphine-induced hyperalgesia in mice. The tail-flick test was used to assess the effects of morphine alone and in combination with the NMDA receptor modulators. 2. Administration of a single low dose (2 mg/kg) of morphine to mice produced antin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…Our finding that MS did not modify the mechanical PWT on the contralateral (non-inflamed) paw, provided evidence that MS does not disturb the behavioral assessment of nociceptive sensitivity in rats. This is supported by previous findings that low doses of MS do not induce any adverse effects in rats [7,23,24].…”
Section: Discussionsupporting
confidence: 90%
“…Our finding that MS did not modify the mechanical PWT on the contralateral (non-inflamed) paw, provided evidence that MS does not disturb the behavioral assessment of nociceptive sensitivity in rats. This is supported by previous findings that low doses of MS do not induce any adverse effects in rats [7,23,24].…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have demonstrated the involvement of enhanced spinal NMDA activity in the loss of antinociceptive efficacy of morphine in nerve‐injured animals, since NMDA antagonists prevented not only the development of hypersensitivity, but also the loss of antiallodynic efficacy of intrathecal morphine (Bian et al., ; Gupta, Gupta, & Tripathi, ; Mao et al., ; Ossipov et al., 1995b). Patients receiving NMDA antagonists, such as ketamine, alongside opioids have also exhibited recovery of opioid analgesic effect (da Cunha Leal, Clivatti, Garcia, & Sakata, ; Lee, Song, Jeong, & Park, ; Pasero & McCaffery, ).…”
Section: Neuropathological Mechanisms Shared By Neuropathic Pain and mentioning
confidence: 99%
“…Central pain sensitization, NMDA receptor activity, and spinal dynorphin release have all been implicated as the source of OIH (Daeninck and Bruera, 1999 ; Gardell et al, 2002 ; Koppert and Schmelz, 2007 ; Gupta et al, 2011 ). OIH is comparable to neuropathic pain in both its neuro-inflammatory qualities and central sensitization processes.…”
Section: Suggested Mechanisms Of Opioid Induced Hyperalgesiamentioning
confidence: 99%